1. The problem statement, all variables and given/known data definition of εijk εijk=+1 if ijk = (123, 231, 312) εijk = −1if ijk = (213, 321, 132) , (1.1.1) εijk= 0,otherwise . That is,εijk is nonzero only when all three indices are different. From the definition in Eq. (1.1.1), show that εijkεinm= δjnδkm − δjmδkn , (1.1.4) where of course there is an implied sum over the i index in Eq. (1.1.4), but the indices j, k, n,and m are free. 2. Relevant equations 3. The attempt at a solution By using definition of εijk; I can show that under the values which i,j,k,n,m can take, L.H.S.=R.H.S. But is there any other better way to show it? Is there a way such that one will start from L.H.S. and reach to R.H.S.?